Using One-Class SVM with Spam Classification - Ali , Inas; Saad , Sumaya; Ahmed , Safa (Iraqi Journal of Science, 2023)
Support Vector Machine (SVM) is supervised machine learning technique which has become a popular technique for e-mail classifiers because its performance improves the accuracy of classification. The proposed method combines gain ratio (GR) which is feature selection method with one-class training SVM to increase the efficiency of the detection process and decrease the cost. The results show high accuracy up to 100% and less error rate with less number of feature to 5 features.